2014
DOI: 10.1155/2014/247258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fascioliasis in Cattle Slaughtered in Sokoto Metropolitan Abattoir, Sokoto, Nigeria

Abstract: The prevalence of fascioliasis in cattle slaughtered in the Sokoto metropolitan abattoir was investigated. Faeces and bile samples were collected and processed using formal ether concentration technique. Gross lesions from 224 out of 1,313 slaughtered cattle were randomly selected and examined. Out of the 224 cattle examined, 95 (42.41%) were males and 129 (57.59%) were females. Out of 95 male cattle examined, 27 (28.42%) were infected and out of 129 females 35 (27.13%) were infected. Based on breed, infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
40
7
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 12 publications
12
40
7
2
Order By: Relevance
“…The work in the present study is in conformity with the work of Mebrahtu and Beka (2013) that worked on prevalence and economic significance of Fasciolosis in cattle slaughtered at Dire Municipal abattoir, Ethiopia which reported higher prevalence in female (25.27%) than male (23.9%). The work in the Present study disagree with the work of Magaji, et al (2014) that worked on prevalence of Fasciolosis in cattle slaughtered at Sokoto metropolitan abattoir, who reported higher prevalence in males 27(28.42%) than female 35(27.13%).Similarly the work of Biniam, et al (2012) also disagrees with the present work, which reported higher prevalence in males (41.43%) than female (41.38%). The prevalence of Fasciolosis in adult cattle was found to be greatly higher (40.3%) than young ones (15.0%).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The work in the present study is in conformity with the work of Mebrahtu and Beka (2013) that worked on prevalence and economic significance of Fasciolosis in cattle slaughtered at Dire Municipal abattoir, Ethiopia which reported higher prevalence in female (25.27%) than male (23.9%). The work in the Present study disagree with the work of Magaji, et al (2014) that worked on prevalence of Fasciolosis in cattle slaughtered at Sokoto metropolitan abattoir, who reported higher prevalence in males 27(28.42%) than female 35(27.13%).Similarly the work of Biniam, et al (2012) also disagrees with the present work, which reported higher prevalence in males (41.43%) than female (41.38%). The prevalence of Fasciolosis in adult cattle was found to be greatly higher (40.3%) than young ones (15.0%).…”
Section: Discussioncontrasting
confidence: 95%
“…The reason for this prevalence could be due to increase in irrigated land masses in the study areaand tendency for animal rearers and farmers to feed the animals in these marshy and damp arrears because of feed scarcity. Since intermediate host prefers swampy arrears with slowly moving water and small streams which also allow sufficient moisture for the survival of the infective metacercariae (Magaji, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…6 About 250 million sheep and 300 million cattle are potentially affected by the fasciolosis world-wide. 7 Over the past three decade fasciolosis is recognized as an important emerging zoonotic disease of human and categorized as neglected tropical disease (NTD). 8 The incidence of human fasciolosis has also been reported in different state of India.…”
Section: Introductionmentioning
confidence: 99%
“…F. gigantica and F. hepatica are the most important liver fluke in the tropics and temperate regions most frequently reported to causing ruminants fasciolosis (Maje et al, 2015). Fasciolosis is prevalent in Nigeria and is of high economic significance especially in northern Nigeria where stagnant water, lakes, dams and ponds are used as watering and grazing areas more especially during dry season (Magaji et al, 2014).…”
Section: Introductionmentioning
confidence: 99%